Implementasi Penegakan Hukum terhadap Penyalah Guna Narkotika Melalui Penghentian Penuntutan Berbasis Keadilan Restoratif - Era Fitriany (Jurnal Hukum Lex Generalis, 2026)
Drug abuse requires treatment that is not only oriented toward punishment, but also toward rehabilitation. This empirical normative legal research examines the implementation of restorative justice-based prosecution termination for drug abusers. The results indicate that restorative justice provisions are already included in the Attorney General's Office's policies, but have not been comprehensively regulated at the legislative level. This mechanism has advantages in terms of offender rehabilitation, reducing prison overcrowding, and increasing access to rehabilitation, but faces weaknesses in terms of limited implementation and oversight standards. The research proposes more comprehensive regulations, including increased officer capacity, integrated assessments and the availability of rehabilitation services as operational measures.